Peningkatan Kualitas Produksi dan Pemasaran Produk Bandeng Presto di UMKM Bandeng Presto “Mbak Sofi” Semarang - Fafa Nurdyansyah; M. Khoiron Ferdiansyah; Arief Rahman Affandi; Umar Hafidz Asyari Hasbullah (Universitas Muhammadiyah Semarang, 2020)
Milkfish is a marine commodity that has a lot of potential to be developed, one of which is soft-boned milkfish in Semarang City. Mbak Sofi's Milkfish Micro, Small and Medium Enterprise (MSME) of “Bandeng Mbak Sofi” is one of the MSMEs that processes fresh milkfish into soft-boned milkfish. However, the milkfish processing in the MSME is still relatively simple and there is no good management of MSME management. This service aims to help Mbak Sofi's milkfish MSME in an effort to increase innovation and quality of the milkfish processing produced and its management. The main problems faced by the partner are the relatively short shelf life of soft-boned milkfish, limited facilities and infrastructure for processing, management of MSME management, and marketing. Some of the steps that will be taken for the implementation of this program are the provision of supporting infrastructure for the processing and the innovation of milkfish processing. In addition, for regulatory processes, PIRT has been issued for soft-boned milkfish products and other products. Lack of creativity in processing can be given a solution by increasing the innovation of milkfish-based products. Production management, finance, distribution and marketing will also be the focus of this program. With the implementation of this service program, the quality of the soft-boned milkfish is better and is able to compete in a wider market.